Approximative properties of biharmonic Poisson integrals on Hölder classes - Hembars'ka, S. B.; Zhyhallo, K. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We establish asymptotic expansions for the values of approximation of functions from the H¨older class by biharmonicPoisson integrals in the uniform and integral metrics.